Population Structure and Genetic Connectivity of Squat Lobsters (Munida Leach, 1820) Associated With Vulnerable Marine Ecosystems in the Southwest Pacific Ocean - Yan, Ruo-Jin; Schnabel, Kareen E.; Rowden, Ashley A.; Guo, Xiang-Zhao; Gardner, Jonathan P. A. (Frontiers in Marine Science, 2020)
Studies of genetic diversity and population genetic structure in deep-sea fauna mainly focus on vulnerable marine ecosystem (VME) indicator taxa, whilst relatively few studies have focussed on VME-associated taxa whose distributions are not exclusively limited to VMEs. Knowledge of genetic connectivity (gene flow) amongst populations of VME-associated taxa, such as squat lobsters, will contribute to ongoing management decision-making related to the protection of VMEs. To better understand the genetic diversity and genetic structure of squat lobster populations (Munida isos, Munida endeavourae and Munida gracilis) at different spatial scales (biogeographic provinces, regions and geomorphic features) in the southwest Pacific Ocean, mitochondrial cytochrome c oxidase subunit I (COI) region and nuclear microsatellite markers were employed. Overall, the levels of genetic diversity were high for the COI region and moderate for the microsatellite loci across the three Munida species. Analysis of molecular variance (AMOVA) of COI variation revealed no significant genetic differentiation, whereas AMOVA of microsatellite variation revealed significant genetic differentiation amongst the three species, but at different spatial scales. Based on microsatellite variation, a range of analyses [Structure, principal coordinate analysis (PCoA), discriminant analysis of principal components (DAPC)] provided some evidence of limited genetic differentiation at different spatial scales across the three species. Low to moderate levels of assignment success (∼40–60%) based on microsatellite variation were achieved for the three Munida species, suggesting high levels of gene flow and possible panmixia. Nonetheless, for M. isos, populations from the Tasmanian slope were genetically differentiated from all other populations and may act as source populations, whereas populations from the Kermadec Ridge region may be sink populations for all three Munida species. Our results highlight the need to consider gene flow at trans-national scales when managing anthropogenic impacts on VMEs. The results are discussed in the context of existing marine protected areas (MPAs), which can contribute new information useful to the management of VMEs within the southwest Pacific Ocean.